2022
DOI: 10.5603/rpor.a2022.0080
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical failure and toxicity in treatment with brachytherapy and external beam radiotherapy compared with radical prostatectomy in localized prostate cancer

Abstract: This article has been peer reviewed and published immediately upon acceptance.It is an open access article, which means that it can be downloaded, printed, and distributed freely, provided the work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 52 publications
1
1
0
Order By: Relevance
“…Similarly, Ye et al (2022) [ 15 ] also found that combining external beam radiotherapy (EBRT) with intraluminal brachytherapy (IBT) offers an effective treatment modality for cancer with maximum local control than EBRT alone. These findings were consistent with the findings established in the study by Galdos-Bejar et al (2022) [ 14 ] by asserting that patients treated with the combination of EBRT + HDBT and RP had less biochemical failure and post-treatment toxicity than patients treated with EBRT + HDBT [ 14 ].…”
Section: Reviewsupporting
confidence: 91%
See 1 more Smart Citation
“…Similarly, Ye et al (2022) [ 15 ] also found that combining external beam radiotherapy (EBRT) with intraluminal brachytherapy (IBT) offers an effective treatment modality for cancer with maximum local control than EBRT alone. These findings were consistent with the findings established in the study by Galdos-Bejar et al (2022) [ 14 ] by asserting that patients treated with the combination of EBRT + HDBT and RP had less biochemical failure and post-treatment toxicity than patients treated with EBRT + HDBT [ 14 ].…”
Section: Reviewsupporting
confidence: 91%
“…Moreover, patients hardly require returning to hospitals as outpatients for radiation treatment. GammaTile therapy is an effective and safe radiation option that hardly requires capital investment and helps eliminate the need for repeat treatments with other related caregivers and transportation burdens [ 14 ].…”
Section: Introductionmentioning
confidence: 99%